Immunophenotyping of selected hematologic disorders – focus on lymphoproliferative disorders with more than one malignant cell population. Issue 3 (17th April 2013) - Porwit, A.
Summary Currently, clinical laboratories face increasing demand for flow cytometry testing combined with limited funding. Therefore, many laboratories search for panels that would provide sufficient immunophenotyping information and meet economical requirements. At the Flow Cytometry Laboratory, University Health Network, Toronto, ON, Canada, we apply two 10‐color tubes of surface markers for diagnosis of lymphoproliferative disorders (LPDs). These tubes contain most of the mandatory B‐ and T‐cell markers according to European Leukemia Net (www.leukemia-net.org) recommendations. The B‐cell‐oriented panel includes the following antibodies: Kappa‐FITC/lambda‐PE/CD19‐ECD/CD38‐PC5.5/CD20‐PC7/CD34‐APC/CD23 APC‐AF700/CD10 APC‐AF750/CD5‐PB/CD45‐KO. A different combination is applied to detect cytoplasmic Ig light chain expression and aberrant immunophenotype of plasma cells. The T‐cell panel allows enumeration of various T‐ and NK‐cell subsets: CD57‐FITC/CD11c‐PE/CD8‐ECD/CD3‐PC5.5/CD2‐PC7/CD56‐APC/CD7‐APC‐AF700/CD4‐APC‐AF750/CD5‐PB/CD45‐KO. The reported overall incidence of B‐cell chronic LPDs presenting with more than one aberrant population is approximately 5%. Multicolor analysis facilitates the detection of multiple aberrant populations in the same sample because expression of multiple antigens can be studied simultaneously in each defined population. Examples of LPDs with multiple aberrant populations are presented.